2012
DOI: 10.1155/2012/189580
|View full text |Cite
|
Sign up to set email alerts
|

Study of Anterior Chamber Aqueous Tube Shunt by Fourier-Domain Optical Coherence Tomography

Abstract: Purpose. This cross-sectional, observational study used Fourier-domain optical coherence tomography (OCT) to examine the position, patency, and the interior entrance site of anterior chamber (AC) aqueous tube shunts. Methods. The OCT, slitlamp biomicroscopy, and gonioscopy findings of 23 eyes of 18 patients with AC shunts were collected and compared. Results. OCT images demonstrated the shunt position and patency in all 23 eyes, and the details of the AC entrance in 16 eyes. The position of the tube varied, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Studies evaluating the corneal endothelium in eyes with AC tube shunts have shown that there is a constant insult to the corneal endothelium near the silicone tube and it has been suggested to place the tube as far from the cornea as possible to protect the corneal endothelium [4,24]. In another study, endothelial contact at the insertion point of the tube was proposed as a risk factor for corneal endothelial cell loss in AC tube shunt surgery and authors recommended entry site of the tube to be posterior to Schwalbe's line to avoid corneal endothelial trauma [25]. In this regard, ciliary sulcus implantation of the tube shunt seems to be more con dent for the corneal endothelium than AC angle.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the corneal endothelium in eyes with AC tube shunts have shown that there is a constant insult to the corneal endothelium near the silicone tube and it has been suggested to place the tube as far from the cornea as possible to protect the corneal endothelium [4,24]. In another study, endothelial contact at the insertion point of the tube was proposed as a risk factor for corneal endothelial cell loss in AC tube shunt surgery and authors recommended entry site of the tube to be posterior to Schwalbe's line to avoid corneal endothelial trauma [25]. In this regard, ciliary sulcus implantation of the tube shunt seems to be more con dent for the corneal endothelium than AC angle.…”
Section: Discussionmentioning
confidence: 99%
“…10 Microscopic fibrotic tissue between the tube and corneal endothelium was detected using highresolution Fourier domain OCT to evaluate anterior chamber tube shunts. 10 Microscopic fibrotic tissue between the tube and corneal endothelium was detected using highresolution Fourier domain OCT to evaluate anterior chamber tube shunts.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported on a loss of CEC density post GDIS, which is thought caused by physical contact of the tube to the cornea at its insertion point [ 29 ], the distance of the tube tip to the cornea [ 30 ], a change in the location of the tube during the postoperative time course [ 31 ], a foreign body reaction against the tube material [ 32 ], or turbulence at the tip of the silicon tube [ 33 ]. Kim et al [ 34 ] reported that post AGV implantation, the mean loss of CEC density per month was − 17.5 cells/mm 2 (0.84%), while that reported by Zhang et al [ 35 ] was − 29.3 cells/mm 2 (1.37%).…”
Section: Discussionmentioning
confidence: 99%